PENGARUH TIKTOK SHOP SEBAGAI MEDIA DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z DI SURAKARTA - R. Chrisharmukti Hartoyo; Edi Purwanto; Elida Zia'ul Huda (JURNAL ILMIAH EDUNOMIKA, 2026)
Background: The development of digital technology and social media has changed consumer behavior in online product purchases. One platform experiencing rapid growth is TikTok Shop, which utilizes various digital marketing strategies to attract consumer interest. Generation Z, as a group actively using social media, is a potential target for digital marketing activities. Objective: To analyze the influence of content quality, interactivity, trust, and brand image on Generation Z purchasing decisions in Surakarta City through TikTok Shop. Method: This study used a quantitative method with a sample of 100 Generation Z respondents in Surakarta City. Data were collected through questionnaires and analyzed using multiple linear regression. Results: The results show that content quality, interactivity, trust, and brand image have a positive and significant influence on Generation Z purchasing decisions in Surakarta City. Interactivity is the most dominant factor, while the model's ability to explain purchasing decisions is 85.5%. Conclusion: Based on the results of the study, it can be concluded that content quality, interactivity, trust, and brand image have a positive and significant influence on Generation Z purchasing decisions in Surakarta City through TikTok Shop. Keywords: Content Quality, Interactivity, Trust, Brand Image, Purchase Decision